Restorative Practices: Using local evidence on costs and student outcomes to inform school district decisions about behavioral interventions. (June 2022) - Hollands, Fiona M.; Leach, Stephen M.; Shand, Robert; Head, Laura; Wang, Yixin; Dossett, Dena; Chang, Florence; Yan, Bo; Martin, Minetre; Pan, Yilin; Hensel, Saundra
Abstract: School disciplinary practices affect student academic and life outcomes. Many schools have recently shifted towards the prevention of behavioral disorders rather than the punishment of such disorders, but disciplinary actions are still disproportionately meted out to Black students. We took advantage of a natural experiment in a large school district to investigate the costs and effects of a school-wide intervention based on the principles of restorative justice on suspensions, referrals, and three school climate constructs. The study involved 14 elementary and middle schools, each of which was already implementing Positive Behavioral Interventions and Supports (PBIS). Six of the schools integrated Restorative Practices into their PBIS framework during the first year of the study, whereas the other eight served as comparison schools and implemented the program the following year. We tested a difference-in-difference regression model for each of our five outcomes of interest after 1 year of implementation using Quasi-Poisson models for referrals and suspensions. We found no statistically significant effects on four of the outcomes, either for the overall sample or by racial subgroup. We found negative effects on student-reported personal safety. An additional analysis 1 year later showed that Black students in schools implementing Restorative Practices for 2 years experienced a greater reduction in suspensions than Black students in schools implementing the program for only 1 year. We used the ingredients method to estimate start-up costs and ongoing costs for the first full year of implementation. Our reference case analysis results using a societal perspective, national average prices, and a 3% discount rate were 57, 450 per school and 139 per student for the first year of Restorative Practices implementation. These estimates included training costs from the prior year and were incremental to the costs of PBIS, which served as the business-as-usual condition. We compared these costs to those of a number of other behavioral interventions and concluded that Restorative Practices are relatively low cost but may need to be implemented for several years with greater fidelity in order to produce the desired improvements in behavior events and school climate.